Pembelajaran Pendidikan Agama Islam di Perguruan Tinggi Umum - Umar Al Faruq (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2020)
Various multidimensional crises that exist in this nation are allegedly due to the failure of religious education. Various cases such as brawls between students, promiscuity, violence, even radicalization and so on are the output of failure to instill religious values ??????being taught. Religious education aims to shape students into human characters, with good character, devoted to God Almighty, able to play a good role in their environment, and to benefit others and the environment around them. Islamic religious education has an important position in the world of education. This paper explores the implementation of Islamic education learning and the phenomenon of radicalism in Brawijaya University. The method used in this research is qualitative. Sources of data obtained from interviews, observation and documentation. The results of the research are 1. Islamic Education learning runs according to existing corridors, only implementation in the field varies based on needs. 2. Learning PAI in UB does not contain radical understanding. Keywords: , ,